The Ten commandments movie storybook - Naha, Ed; Bond, Cindy; Yaxley, Trevor (Singapore : Marshal Cavendish Edition, 2008)
'A delightful educational adventure for children taken directly from the animated feature movie ...'--Cover back.
Koleksi sumbangan Tun Ahmad Sarji Abdul Hamid.
Keywords: Ten commandments -- Juvenile literature; Bible stories, English -- Old Testament -- Juvenile literature; Christian ethics